2013
DOI: 10.1039/c3cc43032d
|View full text |Cite
|
Sign up to set email alerts
|

A poly(3-hexylthiophene) block copolymer with macroscopically aligned hierarchical nanostructure induced by mechanical rubbing

Abstract: A highly ordered, uniformly aligned nanostructure with good crystallinity was first achieved on a P3HT block copolymer possessing a low weight fraction (19.4 wt%) of a flexible polyisoprene segment via a mechanical rubbing process without the use of solution based fabrication and thermal annealing. The attachment of the short polyisoprene segment to P3HT would significantly promote the main chain mobility to allow the orientation control of P3HT and of the self-assembled nanostructure by rubbing.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 24 publications
(1 reference statement)
0
5
0
Order By: Relevance
“…The electrical properties of semiconducting polymers are intimately related to crystal orientation, which can be quantified by Hermans’ orientation factor, f H . Calculated from the first order alkyl stacking (1 0 0) peaks, these factors can range from −0.5 to +1, where 1 corresponds to perfectly oriented crystal planes perpendicular to the substrate (edge-on), −0.5 denotes a lattice plane strictly oriented parallel (face-on), and randomly oriented structures afford a value of 0.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The electrical properties of semiconducting polymers are intimately related to crystal orientation, which can be quantified by Hermans’ orientation factor, f H . Calculated from the first order alkyl stacking (1 0 0) peaks, these factors can range from −0.5 to +1, where 1 corresponds to perfectly oriented crystal planes perpendicular to the substrate (edge-on), −0.5 denotes a lattice plane strictly oriented parallel (face-on), and randomly oriented structures afford a value of 0.…”
Section: Resultsmentioning
confidence: 99%
“…The electrical properties of semiconducting polymers are intimately related to crystal orientation, which can be quantified by Hermans' orientation factor, f H . 40 Calculated from the first order alkyl stacking (1 0 0) peaks, these factors can range from −0.5 to +1, where 1 corresponds to perfectly oriented crystal planes perpendicular to the substrate (edge-on), −0.5 denotes a lattice plane strictly oriented parallel (face-on), and randomly oriented structures afford a value of 0. As shown in Table 1, compared with the other two patterned blade channel geometries, e.g., parallel and prismatic, the films obtained from the blade with wave-like channels provides for the highest f H at 0.64, suggesting a highly oriented microstructure with primarily edge-on orientation.…”
Section: ■ Resultsmentioning
confidence: 99%
“…Conjugated polymers tend to have high melting points, which are associated with close π-stacking which enables interchain charge transport. However, when these conjugated polymers are incorporated into diblock copolymer systems, these high melting points typically cause crystallization to dominate self-assembly. Poly­(3-(2′-ethyl)­hexyl­thiophene) features accessible melting temperatures, while maintaining key features of the many more extensively studied conjugated polymers. In particular, P3EHT in block copolymers leads to robust formation of microphase-separated morphologies and maintains them following crystallization . In lamellar diblock copolymer confinement, the P3EHT crystallite orientation is templated relative to the diblock interface.…”
Section: Introductionmentioning
confidence: 99%
“…Very limited works related to P3HT-PI BCPs have been reported which suggested that PI could potentially modulate the packing of P3HT toward better organization. For example, our previous work demonstrated polyisoprene- block -poly­(3-hexylthiophene)- block -polyisoprene (PI- b -P3HT- b -PI) triblock copolymers would enhance π–π stacking of P3HT in the spin-coated thin film as compared to the pristine P3HT. , Deribew et al utilized P3HT- b -PI diblock copolymers as compatibilizers in P3HT/PCBM bulk heterojunction solar cells to alter the crystallization of P3HT, leading to improved photovoltaic performance . Hereby, we aimed to synthesize P3HT- b -PI diblock and PI- b -P3HT- b -PI triblock copolymers with various compositions and to systematically explore the assembly behaviors of these BCPs.…”
Section: Introductionmentioning
confidence: 99%